Electrochromic Smart Windows Can Achieve an Absolute Private State through Thermochromically Engineered Electrolyte. Issue 21 (17th April 2019) - Wang, Mi; Xing, Xing; Perepichka, Igor F.; Shi, Yuhao; Zhou, Deyun; Wu, Peiheng; Meng, Hong
Abstract: Smart windows regulate the indoor solar radiation by adjusting their optical transmissive properties, offering an efficient way toward energy‐saving buildings, vehicles, etc. Electrochromism is one of the most promising solutions due to its simple control, versatile colors. Yet, electrochromics cannot give zero‐transmission through the whole visible range, leading to the windows that can always be looked through and limited for applications in the public sector. In this work, poly( N ‐isopropylacrylamide) (PNIPAm) hydrogel, which undergoes temperature‐stimulated phase transition from a highly transparent state to a highly scattered zero‐transmission state through the whole visible range is used in the electrolyte of the electrochromic devices without affecting their electrochromic performance. It can be universally applied to inorganic and organic electrochromic devices, and the phase transition temperature can be easily tuned by the ion concentration. Therefore, apart from its ion conductive function, the electrolyte performs the chromatic transition function as well, allowing the electrochromic devices to achieve a zero‐transmissive, absolute "private" state. This chromatic engineering of the electrolyte can significantly broaden the industrial market of electrochromic smart window applications from public to private circumstances and bring much more flexibility in building façades design, which is a remarkable pavement for further industrial applications. Abstract : A new concept of design of electrochromic smart windows combining electrochromism in the active layer and thermochromism in the electrolyte layer has been proposed. Thermochromic transition in the electrolyte from transparent to highly scattered state allows to achieve "absolute private state" of the devices with zero transmission.